PERAN MEDIASI PENGENDALIAN INTERNAL DAN BUDAYA ETIS TERHADAP TINDAKAN FRAUD - Fadly Chandra; Suwandi NG; Cherly Tanamal (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
The purpose of this study was to investigate the role of ethical culture mediation and internal control in the relationship between anti-fraud investment and fraud in the banking sector in Makassar. The research sample used purposive sampling method. The data collection technique used a survey method with a questionnaire. The population of this study were managers or heads of departments who worked in banking companies in Makassar with a total of 120 respondents. Path analysis and sobel test were used to test this hypothesis. The results of this study indicate that the perceived increase in anti-fraud investment has a positive effect on the mediating variables of ethical culture and internal control. Ethical culture mediates the negative and significant influence between anti-fraud investment and fraud. These findings imply that investing in an ethical culture is more effective in preventing fraud.